PENERAPAN ALGORITMA EXPECTATION-MAXIMIZATION (EM) DALAM MENGELOMPOKKAN POPULARITAS OBJEK WISATA DI MALANG RAYA BERDASARKAN INDIKATOR BANYAK PENGUNJUNG - Nur Atikah; Swasono Rahardjo; Trianingsih Eni Lestari; Lucky Tri Oktoviana (Jurnal Kajian Matematika dan Aplikasinya (JKMA), 2021)
The Malang Raya Area is one of the tourist destinations in East Java..Batu City is an area of Malang Raya which is visited by many for sightseeing. Given the development of tourism in Malang Raya, it is necessary to classify the popularity of tourist objects so that they can be used as a reference in policymaking by the tourism office and tourism object managers. In this study, the Expectation Maximation (EM) algorithm is used to determine the clustering of tourist objects in Malang Raya using data on the number of visitors. The results of grouping the popularity of leading tourist attractions in Malang Raya based on the number of visitors are divided into 5 groups, namely: Group 1: Selecta; Group 2: Balekambang, Wendit Baths, and Brawijaya Souvenir Tour; Group 3: Transport Museum, Coban Rondo, Animal Museum, Jatim Park, BNS, Picking Apples “Makmur Abadi and Agro Wonosari Tea Plantation; Group 4: Kusuma Agro Wisata, Kampoeng Kidz, Cangar Hot Springs, Eco Green Park, Predator Fun Park, Coban Rais Tourism Area, Mount Banyak, Mahajaya T-Shirt & Souvenirs, Ngliyep and Selorejo Dam; Group 5: “Dammadhipa Arama” Temple, “Kaliwatu” Rafting, Batu Rafting, Coban Talun Tourism Wana, Tirta Nirwana Baths, Songgoriti Natural Hot Springs, Wonderland Waterpark, Friends of Water Rafting, Independent Apple Picking, Apple Agro Stone, Tourism Village.